Nanoscale curcumin-based metal organic framework material and preparation method thereof
By uniformly mixing curcumin and metal salt in the solvent, and performing dilution and light-proof reactions, nano-sized curcumin zinc MOF materials were successfully prepared, solving the complexity and efficiency of the preparation of nano-sized MOF materials in the prior art, and achieving rapid, simple preparation and good biological performance of the materials.
Patent Information
- Application Number
- CN202411982935.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to quickly, efficiently and with low energy consumption to prepare curcumin zinc metal organic frame materials with nano-scale particle size, and the synthesis method is complex.
The preparation of nano-sized curcumin zinc MOF material is achieved by uniformly mixing curcumin and metal salt in the solvent, and a high concentration of curcumin metal ion complex solution is prepared, and diluting and light-proof reaction is carried out under stirring conditions.
The rapid and simple preparation of nano-scale MOF materials is achieved. The material is spherical and has a particle size of 50-1000nm, and has good antibacterial and antioxidant properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and specifically relates to a nano-scale size-controllable curcumin-based metal organic framework material and a preparation method thereof. Background Art
[0002] Metal-organic frameworks (MOFs) assembled from inorganic metal ions / clusters and organic ligands have attracted much attention due to their flexibility in geometry, size, and composition. Curcumin, a natural compound found in turmeric, has been extensively studied for its antioxidant, anti-inflammatory, anticancer, and antimicrobial properties, which may aid in potential disease prevention. Studies have shown that curcumin-metal ion complexes, such as those containing zinc and copper, are beneficial for enhancing free radical scavenging capacity and exhibiting stronger antimicrobial activity than curcumin, which could be used to enhance the pharmacological effects of curcumin.
[0003] In the biomedical field, the materials used in organisms usually involve issues of in vivo transport and release, so there are certain requirements for the particle size of the materials, which is generally submicron or below. Although there have been many studies on curcumin-based MOFs, it is still difficult to produce MOFs with nanoscale particle sizes, and the synthetic methods involved are usually more complicated. It is still challenging to obtain nanoscale MOFs with high conversion rates from curcumin-zinc mixtures. Further exploration of the preparation methods of nanoscale MOFs that are fast, efficient, low in energy consumption, and can achieve controllable particle size regulation has important research and application significance. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for simply and quickly preparing a nano-scale curcumin zinc MOF with uniform morphology and size and controllable particle size in view of the problems and shortcomings of the prior art.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for preparing a nanoscale curcumin-based metal organic framework material comprises the following steps:
[0007] 1) uniformly mixing curcumin and metal salt in a solvent to prepare a high concentration curcumin metal ion complex solution;
[0008] 2) Under stirring conditions, the solvent described in step 1) is added to the obtained high concentration curcumin metal ion complex solution for dilution, and the obtained dilution is subjected to light-protected reaction, centrifuged, and washed to obtain a nano-scale curcumin zinc MOF material.
[0009] In the above scheme, the metal salt can be selected from one or more of zinc salt and copper salt.
[0010] In the above scheme, the molar ratio of the metal salt to curcumin is 1:0.66-2.
[0011] Furthermore, the zinc salt can be selected from one or more zinc acetate and the like; the copper salt can be selected from one or more copper acetate and the like.
[0012] Furthermore, the metal salts include zinc salts and copper salts, and the introduction of copper salts can improve the activity of superoxide dismutase.
[0013] Furthermore, the molar ratio of the zinc salt to the copper salt is 1:(0-0.25).
[0014] In the above scheme, the solvent comprises anhydrous ethanol.
[0015] Furthermore, the solvent contains anhydrous ethanol and N,N-dimethylformamide.
[0016] Furthermore, the volume ratio of anhydrous ethanol to N,N-dimethylformamide is 1:1-2.4, and the preferred volume ratio is 1:2.3-2.4.
[0017] In the above scheme, the concentration of curcumin in the high-concentration curcumin metal ion complex solution is 24-48 mmol / L.
[0018] In the above scheme, the stirring rate is 300-1000 rpm.
[0019] In the above scheme, the concentration of curcumin in the diluent is 0.4-9 mmol / L.
[0020] Preferably, in the diluent, the concentration of curcumin is 0.5 to 4 mmol / L; more preferably 0.5 to 4 mmol / L; and the particle size of the obtained MOF material is controlled to be less than 500 nm.
[0021] In the above scheme, the total concentration of metal ions in the diluent is 0.75-10 mmol / L.
[0022] Preferably, in the diluent, the total concentration of metal ions is 0.75 to 6 mmol / L; more preferably 0.75 to 1 mmol / L.
[0023] In the above scheme, the light-proof reaction time is 0.5 to 24 hours.
[0024] The nano-scale curcumin zinc MOF material prepared according to the above scheme is spherical and has a particle size of 50 to 1000 nm; and the curcumin-based metal organic framework can achieve controllable adjustment of the particle size at the nanoscale, and the obtained material has good antibacterial and antioxidant properties.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1) The present invention first prepares a high-concentration curcumin-metal ligand solution, dilutes it to form a uniform, low-concentration curcumin-metal ligand solution, and then uniformly nucleates at room temperature and in the dark to achieve uniform growth of MOF in the solution, thereby obtaining a spherical nano-sized MOF material with relatively uniform morphology and size;
[0027] 2) The nano-scale curcumin-based MOF material obtained by the present invention has a broad-spectrum bactericidal effect and good biosafety, and can also remove ROS (·OH, ·O 2- etc.), thereby effectively promoting wound healing;
[0028] 3) The preparation method of the present invention is simple, the raw material source is simple, the cost is low, the reaction conditions are mild, the cycle is short, and the particle size of the curcumin-based metal organic framework material can be controlled and adjusted. It has good biosafety and is suitable for promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The scanning electron microscope images and particle size distribution diagram of the MOF materials obtained under different copper doping conditions, different metal ion and curcumin concentration conditions in Example 2;
[0030] Figure 2 This is a scanning electron microscope image of the MOF material obtained in Comparative Example 1;
[0031] Figure 3 This is a scanning electron microscope image of the MOF material obtained in Comparative Example 2;
[0032] Figure 4 is the removal efficiency of ABTS·+ by MOF materials obtained under different copper doping conditions;
[0033] Figure 5 is the removal efficiency of DPPH· by MOF materials obtained under different copper doping conditions;
[0034] Figure 6 is the scavenging efficiency of ·OH by MOF materials obtained under different copper doping conditions;
[0035] Figure 7 The MOF materials obtained under different copper doping conditions have an influence on the ·O 2- The removal efficiency;
[0036] Figure 8 The cell compatibility of MOF materials obtained under different copper doping conditions with HUVEC cells;
[0037] Fig. 9Plate count photos of S. aureus obtained from MOFs under different copper doping conditions;
[0038] Fig.10 The antibacterial efficiency of MOF materials obtained under different copper doping conditions against S. aureus;
[0039] Fig.11 Plate count photos of E. coli obtained from MOF materials under different copper doping conditions;
[0040] Fig.12 The antibacterial efficiency of MOF materials obtained under different copper doping conditions against E. coli. DETAILED DESCRIPTION
[0041] The technical solutions adopted in the present invention are described in detail below through specific implementation examples, which are only part of the present invention and do not represent all embodiments. Unless otherwise specified, the experimental methods adopted in the present invention are all conventional methods, and the instruments and equipment adopted are all commercial products in the field of this technology.
[0042] Example 1
[0043] A nano-scale curcumin zinc MOF material, the preparation method of which comprises the following steps:
[0044] 1) preparing a mixed solvent of DMF and anhydrous ethanol (the volume ratio of DMF to anhydrous ethanol is 7:3), uniformly dispersing zinc acetate dihydrate and curcumin (Cur) in the obtained mixed solvent, and obtaining a high concentration of curcumin metal ion complex solution, wherein Zn 2+ The concentration of is 36mM, the concentration of Cur is 24mM;
[0045] 2) Then, 0.21 mL of the high concentration curcumin metal ion complex solution was added to a beaker, and 9.79 mL of the mixed solvent described in step 1) was added for dilution. The speed was set to 500 rpm. The resulting dilution (metal ion Zn 2+ The mixture was stirred in the dark for 30 minutes and then centrifuged and washed with anhydrous ethanol for 4 times to obtain curcumin zinc MOF, which was dispersed and stored in anhydrous ethanol.
[0046] Example 2
[0047] A series of nano-scale curcumin zinc / copper MOF materials of different sizes were prepared in the same manner as in Example 1, except that:
[0048] 1) In the high concentration curcumin metal ion complex solution prepared in step 1), the concentration of metal salt (Zn 2+, Cu 2+ ) are: Zn 2+ 36mM+Cu 2+ 0mM (0%Cu 2+ );Zn 2+ 34.2mM+Cu 2+ 1.8mM (5%Cu 2+ );Zn 2+ 32.4mM+Cu 2+ 3.6mM (10%Cu 2+ );Zn 2+ 28.8mM+Cu 2+ 7.2mM (20%Cu 2+ );
[0049] 2) The volumes of the high concentration curcumin metal ion complex solution added in step 2) are: 0.21mL, 0.42mL, 0.84mL, 1.68mL, and the amounts of the mixed solvents used for dilution are: 9.79mL, 9.58mL, 9.16mL, 8.32mL, respectively; wherein, in the obtained dilution, the total metal ion concentration (Zn 2+ +Cu 2+ ) and curcumin concentrations include: metal ion 0.75mM, curcumin 0.5mM; metal ion 1.5mM, curcumin 1mM; metal ion 3mM, curcumin 2mM; metal ion 6mM, curcumin 4mM.
[0050] Figure 1 From the scanning electron microscope images and particle size distribution diagrams of the obtained MOF products at different final dilution concentrations, it can be seen that: using the preparation method described in the present invention, the ratio of the final dilution concentration to copper ions will not affect the morphology of MOF, all of which are spherical in shape and size. The reduction of the final dilution concentration is conducive to obtaining MOF products with smaller particle sizes; the reduction of the proportion of copper ions is conducive to obtaining MOF products with smaller particle sizes, and vice versa.
[0051] The present invention adopts a simple, rapid and low-energy consumption method to obtain a nano-scale curcumin zinc MOF material with a median particle size of less than 400 nm.
[0052] Comparative Example 1
[0053] A curcumin zinc / copper MOF material, the preparation method of which comprises the following steps:
[0054] According to the concentration information corresponding to the dilution described in Example 1, the proportionally weighed curcumin and zinc acetate dihydrate were directly added to a mixed solvent (the volume ratio of DMF to anhydrous ethanol was 7:3) to prepare a dilute solution, and then stirred (500 r / min) in the dark for 30 minutes, centrifuged, and washed with anhydrous ethanol 4 times.
[0055] The electron microscope image of the MOF product obtained in Comparative Example 1 is shown in Figure 2 It can be seen that the generated MOF particles are uneven in size and have an amorphous and partially agglomerated morphology.
[0056] Comparative Example 2
[0057] A curcumin zinc / copper MOF material, the preparation method of which comprises the following steps:
[0058] According to the concentration information corresponding to the dilution described in Example 1, curcumin and zinc acetate dihydrate were first dissolved in a mixed solvent (the volume ratio of DMF to anhydrous ethanol was 7:3) to obtain a dilute solution of curcumin and a dilute solution of zinc acetate, respectively; then the two dilute solutions were mixed, stirred (500 r / min) in a dark environment for 30 min, centrifuged, and washed with anhydrous ethanol 4 times.
[0059] The electron microscope image of the MOF product obtained in Comparative Example 2 is shown in Figure 2 , it can be seen that the generated MOF particles are of different sizes and have an amorphous morphology.
[0060] Comparative Example 3
[0061] A curcumin zinc / copper MOF material, the preparation method of which is substantially the same as that of Example 1, except that the metal salt zinc acetate is replaced by zinc chloride or zinc nitrate.
[0062] In the above reaction system, the anions introduced into the metal salt will affect the system, affecting the nucleation and growth of MOF, and ultimately leading to problems such as failure to nucleate or formation of amorphous MOF; the MOF material with uniform morphology and size as described in the present invention cannot be obtained. The performance test results of the nano-scale curcumin metal MOF material obtained by the preparation method of the present invention are as follows:
[0063] (1)ABTS ·+ Clear
[0064] Prepare 1 mL of 5.5 mM ABTS + Deionized water solution, 1 mL 2.7 mM K 2 S 2 O 8 Deionized water solution, mix the two, add deionized water to 10mL, keep overnight in dark conditions, dilute 15-20 times when used, so that the absorbance of the control group is 0.7-0.8. Then prepare Zn-Cur and Zn-Cu-Cur dispersions of different concentrations (0, 40, 80, 120, 160, 200μg / mL), take 200μL of material dispersion in each group, add to 600μL ABTS ·+The final concentration of the material was maintained at 0, 10, 20, 30, 40, 50 μg / mL), incubated in the dark for 30 min, centrifuged, 200 μL of the supernatant was taken, and then the absorbance at 734 nm was measured with an ELISA reader. The experiment was repeated three times. + The clearance formula is as follows:
[0065]
[0066] In the formula, A 0 For the original ABTS + The absorbance of the blank solution; A 1 For ABTS ·+ The absorbance of the solution after incubation with various concentrations of material.
[0067] (2) DPPH removal
[0068] Prepare 0.4mM DPPH ethanol solution, and store it in dark conditions after fully dissolving. Prepare Zn-Cur and Zn-Cu-Cur dispersions of different concentrations (0, 20, 40, 60, 80, 100μg / mL) with ethanol, take 400μL of the material dispersion and add it to an equal volume of DPPH solution, incubate for 30mins, centrifuge, take the supernatant, and test the absorbance at 517nm with an enzyme marker. Repeat the experiment three times.
[0069] The clearance rate of DPPH· is shown as follows:
[0070]
[0071] In the formula, A 0 is the absorbance of the blank control of the original DPPH solution; A 1 It is the absorbance of DPPH solution after incubation with materials of various concentrations.
[0072] (3) OH removal
[0073] SA was used as a specific probe to detect the scavenging ability of different materials and their concentrations on ·OH. 2+ / H 2 O 2 The system produces ·OH through Fenton reaction. Zn-Cur and Zn-Cu-Cur can remove part of ·OH, while the remaining ·OH can be captured by SA to generate purple 2-hydroxysalicylic acid. The ·OH content in the system can be known by detecting the absorbance at 510 nm. Different concentrations of FeSO 4 (2mM), H 2 O 2(5mM), SA (1.5mM) solution, and Zn-Cur and Zn-Cu-Cur dispersions of different concentrations (0, 12.5, 25, 50, 100 and 200μg / mL). The system was incubated at 37°C for 30min, and its absorbance at 510nm was measured using an ELISA reader.
[0074] The calculation formula of OH removal rate is as follows:
[0075]
[0076] Where A0 is the absorbance of the blank control; A1 is the absorbance after incubation with various concentrations of materials.
[0077] (4) ·O 2 - Clear
[0078] NBT colorimetric test 2 - First, riboflavin (20 μM) and L-methionine (13 mM) solutions were mixed and reacted for 5 mins to generate ·O 2 - , centrifuge and take the supernatant, then add different concentrations (0, 20, 40, 60, 80, 100 μg / mL) of Zn-Cur and Zn-Cu-Cur in PBS (PH=7.4, 10 mM), incubate for 20 mins, centrifuge, take the supernatant, and finally irradiate with a constant light intensity LED light for 3 mins, and immediately test the absorbance at 560 nm with an enzyme marker. The experiment was repeated three times.
[0079]
[0080] Wherein, A0 is the absorbance of the control group without adding materials and irradiating with light; A1 is the absorbance of the material group after incubation with various concentrations of materials and irradiating with light.
[0081] (5) In vitro antibacterial performance test
[0082] The plate colony counting method was used to test the anti-S. aureus and E. coli abilities of Zn-Cur and Cu-Zn-Cur. The bacterial suspension was diluted to 1×10 8 CFU / mL, 100 μL was added to a 96-well plate, and then 100 μL of the material was added to the 96-well plate to keep the final concentration of the material at 0, 1.25, 2.5, 5, 10 and 20 μg / mL, and incubated together in a 37°C incubator for 5 h. After dilution (during the entire experiment, S. aureus was diluted 2.5×10 6 times, E. coli diluted 1.6×106 100 μL of bacterial solution (multiplied by 100 μL) was evenly spread on the LB agar plate. After continuing to culture in an incubator at 37°C for 20 hours, the number of colonies on the agar plate was counted and the antibacterial efficiency was calculated using the following formula:
[0083]
[0084] Wherein, CFU0 is the number of colonies on the agar plate of the blank control group; CFU1 is the number of colonies on the agar plate of the group incubated with materials of various concentrations.
[0085] (6) The cytotoxicity of HUVEC cells was detected by MTT method, with 1×10 4 HUVEC cells were inoculated into 96-well plates at a density of 10 cells, and the wells were placed in a 37°C cell culture incubator for 24 hours after adding the cell suspension. After the cells were completely attached to the wall, the supernatant was removed, and different concentrations (0, 5, 10, 20, 40 and 60 μg / mL) of Zn-Cur and Cu-Zn-Cur dispersions were added to each well of the well plate and continued to be cultured for 24 hours. After the culture was completed, 9% MTT solution was added, and incubated at 37°C for 4 hours, after which the MTT solution was aspirated, and 150 μL of DMSO was added to each well to dissolve the purple formazan at the bottom of the well plate, and then the absorbance at 490 nm was scanned with an ELISA reader.
[0086]
[0087] Where A0 is the absorbance of the blank control; A1 is the absorbance after incubation with various concentrations of materials.
[0088] Finally, it should be noted that the technical solutions implemented above are examples, which are only used to illustrate the technical solutions of this article, rather than to limit them. For those of ordinary skill in the art, they can still make modifications and replacements based on the examples, which obviously belong to the protection scope of the present invention. The present invention is not limited to the above-mentioned embodiments, but also has many other variations. According to the technical essence of the present invention, simple modifications and changes to the embodiments are made, without departing from the technical solution ideas of the present invention, and are all described in the protection scope of the present invention.
Claims
1. A method for preparing a nanoscale curcumin-based metal organic framework material, characterized in that: The steps include: 1) uniformly mixing curcumin and metal salt in a solvent to prepare a high concentration curcumin metal ion complex solution; 2) Under stirring conditions, the solvent described in step 1) is added to the obtained high concentration curcumin metal ion complex solution for dilution, and the obtained dilution is subjected to light-protected reaction, centrifuged, and washed to obtain a nano-scale curcumin zinc MOF material.
2. The preparation method according to claim 1, characterized in that: The metal salt is one or more of zinc salt and copper salt.
3. The preparation method according to claim 1, characterized in that: The zinc salt is zinc acetate; the copper salt is copper acetate.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the metal salt to curcumin is 1:0.66-2.
5. The preparation method according to claim 1, characterized in that: The solvent includes anhydrous ethanol.
6. The preparation method according to claim 1, characterized in that: The solvent comprises anhydrous ethanol and N,N-dimethylformamide.
7. The preparation method according to claim 1, characterized in that: In the high-concentration curcumin metal ion complex solution, the concentration of curcumin is 24-48 mmol / L.
8. The preparation method according to claim 1, characterized in that: In the diluent, the concentration of curcumin is 0.75-9 mmol / L.
9. The preparation method according to claim 1, characterized in that: The light-proof reaction time is 0.5 to 24 hours.
10. The nano-scale curcumin zinc MOF material obtained by the preparation method according to any one of claims 1 to 9, characterized in that: It is spherical and its particle size is 50 to 1000 nm.
Citation Information
Cited By
Curcumin ratiometric fluorescent sensor fluorescent probe, curcumin and curcumin derivative detection method and device
CN121471535A